Pengaruh Karakteristik PerusahaanTerhadap Reaksi Pasar Modal: Studi Empiris Pada Perusahaan Yang Termasuk Dalam Indeks SRI-KEHATI Tahun 2009-2011 - Eka Noor Asmara (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2017)
Aim of this research is to detect empirical effects of corporate characteristic to capital market reaction which is revealed by abnormal return in the corporate social responsibility disclosure period. The disclosures include details of the environment, energy, employee health and safety, products, community involvement, and general. Previous researches that have been reviewed show the inconsistencies which are contribute substantially to the diversity of result. This research attempts to straighten by using three corporate characteristics as explanatory variables. They are company size, profitability, and leverage. Sampling technique that is used in this research is non-probability sampling by purposive sampling technique. Corporates that have been observed should be included in the SRI-KEHATI index during observation process. Number of company for research sample is 19 companies. To verify market reaction, this research used abnormal return as a dependent variable. Hyphothesis test was conduct by using double regression analysis. By using variable test of company size (H1), leverage ratio (H2), and profitability ratio or return on equity (H3), this research revealed that elements having impacts to abnormal return are leverage ratio and profitability or return on equity while company size has not having significant impact. It is mean that the investors still consider leverage ratio and profitability or return on equity ratio as variable to make investment decision to companies that periodically report corporate social responsibility in the published financial report.